Art 21 art in the 21st century. Seasons four (Art21, Inc. ;distributed by PBS Home Video, 2005)
What goes on inside the minds of today's most dynamic visual artists? How do they make the leap between insight and finished object? What inspires artists to break through the barriers of convention to arrive at new way of seeing? These and other intriguing questions are explored in Season Three of "Art:21--Art in the Twenty-First Century," the only series on national public television to focus exclusively on contemporary art and the people who create it. Like the great biennial art exhibitions that regularly showcase current artistic activity, Art:21 returns to television every two years to profile working artists who build our living culture with each painting, sculpture, photograph or installation that they create. [from pbs.org].